Analisis Kesalahan Penggunaan Afiks dalam Makalah Mahasiswa Semester 1 Program Studi Pendidikan Bahasa Indonesia Universitas Al Asyariah Mandar - Adelia Sulastri; Nur Hafsah Yunus MS; Rina Riniawati (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
This research is based on the problem of the many errors in the use of affixes in students' papers or scientific papers. This affects the various changes in meaning caused by affixes. This study aims to describe the errors in the use of affixes contained in the first semester student papers in the Indonesian language study program at Univeristas Al Asyariah Mandar. This type of research is descriptive qualitative. The instrument used in this study was the human instrument. The data collection technique used is the note taking technique. The object under study is a paper written by a student. The results showed that from 14 research sources 32 data were produced and there were three types of errors in the use of affixes, namely prefixes, confixes, and simulfices. As for the prefix error, which is 1 error or 3.13%, there are 18 errors or 56.25% and 1 error or 3.13%. Errors in the use of confixes, namely as many as 1 error or 3.13%, and as many as 8 errors or 25.00% and in-i as much as 1 error or 13.13%. Error in using simulfix, which is 2 errors or 6.25%. Based on the results of data analysis that has been done, it can be concluded that students make a lot of mistakes in the use of pre-prefixes. In addition, various spelling errors were also found. Therefore, mastering affixes and spelling needs to find a solution.